Chromium-free hot galvanizing anticorrosion passivation solution and preparation method thereof

By modifying the chromium-free anti-corrosion passivation solution composed of heteropoly acids, aqueous resins, phosphates, nitrates and nano-silica, the environmental pollution problem of traditional chromate anti-corrosion passivation solution is solved, and the hot plating is significantly improved The corrosion resistance of zinc plates achieves environmentally friendly and efficient anti-corrosion effects.

CN119243136APending Publication Date: 2025-01-03YANGJIANG POWER SUPPLY BUREAU OF GUANGDONG POWER GRID
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411589089.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Traditional hot-dip galvanized steel plates are prone to corrosion in humid and hot environments, and the chromate anti-corrosion passivation liquid used has problems of environmental pollution and health threats.

Method used

The chromium-free hot-dip galvanized anti-corrosion passivation solution consisting of rare earth modified heteropoly acids, aqueous resins, phosphates, nitrates and nano-silicas is used to improve the corrosion resistance of the galvanized layer by forming a dense protective film, and the corrosion resistance of the galvanized layer is improved through Sol-gel method to prepare rare earth modified heteropoly acids to improve their stability.

Benefits of technology

The environmental protection and efficiency of chromium-free anti-corrosion passivation liquid is achieved, which significantly improves the corrosion resistance of hot-dip galvanized plates, extends the service life, and reduces the harm of chromium emissions to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125074590000091
    Figure BDA0005125074590000091
  • Figure BDA0005125074590000101
    Figure BDA0005125074590000101
Patent Text Reader

Abstract

The invention discloses a chromium-free hot galvanizing anticorrosion passivation solution which is prepared from rare earth modified heteropoly acid, water-based resin, phosphate, nitrate, nano silicon dioxide and a polar solvent. The anti-corrosion passivation solution can form a compact protective film on the surface of a zinc coating, does not contain a chromium element, reduces the influence of chromium emission on the environment and human health, is more environmentally friendly, and better meets the current environmental protection requirement. The rare earth modified heteropoly acid is introduced into the anti-corrosion passivation solution, so that the corrosion resistance of the treated hot-dip galvanized plate is remarkably improved, and the service life of the hot-dip galvanized plate can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of metal surface treatment agents, and in particular to a chromium-free hot-dip galvanizing anti-toxic passivation solution and a preparation method thereof. Background Art

[0002] As an important part of the power system, the transmission and distribution lines are of great significance to the safe and stable operation of the entire power grid. For the field of power transmission and transformation, the anti-corrosion passivation of metals is very important because it is related to the safety and reliability of power grid equipment. Due to the complex and changeable environmental conditions, such as humidity, temperature, salt spray, etc., metal components will be corroded, thus affecting the stability and safety of the power grid. Therefore, the adoption of effective anti-corrosion passivation measures, such as passivation treatment after galvanizing, can significantly improve the corrosion resistance of metal materials, extend service life, reduce maintenance costs, and thus ensure the safe operation of the power grid.

[0003] Hot-dip galvanizing is the most widely used and cost-effective steel surface treatment method in the world. The hot-dip galvanizing process can coat every part of the plated part with zinc, even in recessed areas, corners and hidden areas, ensuring that the entire steel surface is protected. The galvanizing process is faster than other coating construction processes, and it can also avoid the time required for painting on the construction site after installation, thereby improving construction efficiency. Finally, the cost of hot-dip galvanizing for rust prevention is relatively low, lower than the cost of other paint coatings, and has high economic practicality.

[0004] Hot-dip galvanized steel sheets are prone to corrosion in hot and humid environments, forming white spots or generating gray substances on the surface, which affects the service life and aesthetics of hot-dip galvanized steel sheets. Therefore, the galvanized layer needs to be passivated to improve its corrosion resistance. Chromates are used in traditional anti-corrosion passivation solutions for passivation. Hexavalent chromium is a highly toxic and carcinogenic substance that poses a serious threat to the environment and human health. Chromium salts are heavy metal salts, and large amounts of discharge in wastewater will harm the environment.

[0005] With the continuous development of the economy and society, people's environmental awareness is becoming stronger and stronger. The development of an environmentally friendly, efficient and economical chromium-free anti-corrosion passivation liquid product is conducive to protecting the environment, occupying market share, and has far-reaching economic value and social significance. Summary of the invention

[0006] The purpose of the present application is to provide a chromium-free hot-dip galvanizing anti-corrosion passivation solution with good corrosion resistance and environmental tolerance.

[0007] Another object of the present application is to provide a method for preparing a chromium-free hot-dip galvanizing anti-corrosion passivation solution, which is simple and environmentally friendly.

[0008] To achieve the above objectives, the technical solution adopted in this application is: to provide a chromium-free hot-dip galvanizing anti-corrosion passivation liquid, which is made of rare earth modified heteropoly acid, water-based resin, phosphate, nitrate, nano-silica and polar solvent.

[0009] As a preference, the addition amount of the rare earth modified heteropoly acid is 5% to 20% of the total mass of the anti-corrosion passivation solution.

[0011] As another preferred embodiment, the invention is prepared from 5% to 20% rare earth modified heteropoly acid, 12% to 25% water-based resin, 3% to 10% phosphate, 5% to 15% nitrate, 0.1% to 0.5% nano silicon dioxide, and the balance polar solvent.

[0012] As another preferred embodiment, the invention is made of 5% rare earth modified heteropoly acid, 12% water-based resin, 10% phosphate, 15% nitrate, 0.1% nano silicon dioxide and the balance polar solvent, based on mass fraction.

[0013] As another preferred embodiment, the rare earth modified heteropoly acid is prepared from a metal precursor, a rare earth element compound, a heteropoly acid and other additives by a sol-gel method.

[0014] As another preferred embodiment, the preparation method of the rare earth modified heteropoly acid is as follows: the metal precursor, alcohol solution and strong acid are mixed in a certain proportion, and then the rare earth element compound, the heteropoly acid and a surfactant are added to obtain a mixture, the mixture is subjected to ultrasonic dispersion treatment for a period of time, and allowed to stand to form a gel, and the dried gel is ground to obtain the rare earth modified heteropoly acid.

[0015] As another preferred embodiment, the rare earth element compound is La(NO 3 ) 3 or Ce(NO 3 ) 4 , the heteropoly acid is any one of phosphotungstic heteropoly acid, phosphomolybdic heteropoly acid, and silicotungstic heteropoly acid.

[0016] Further preferably, the water-based resin is any one or more combinations of water-based acrylic resin, water-based polyurethane resin, water-based epoxy resin, water-based alkyd resin, water-based polyester resin, water-based phenolic resin, and water-based amino resin; the phosphate is any one or more combinations of sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and sodium hexametaphosphate; the nitrate is any one or more combinations of sodium nitrate, potassium nitrate, ammonium nitrate, calcium nitrate, magnesium nitrate, and barium nitrate.

[0017] The present application also provides a method for preparing a chromium-free hot-dip galvanizing anti-corrosion passivation liquid, comprising dispersing phosphate and nitrate in a polar solvent, adding a rare earth modified heteropoly acid and uniformly dispersing the same to obtain a first solution; dispersing nano silicon dioxide in an aqueous resin to form a second solution; and adding the first solution dropwise into the second solution under continuous stirring, continuously stirring to mix the two solutions evenly, and standing the solution for a period of time for use.

[0018] As a preferred embodiment, let it stand for more than 24 hours.

[0019] Compared with the prior art, the beneficial effects of this application are:

[0020] (1) The anti-corrosion passivation solution of the present application can form a dense protective film on the surface of the galvanized layer while not containing chromium, thereby reducing the impact of chromium emissions on the environment and human health, being more environmentally friendly and more in line with current environmental protection requirements;

[0021] (2) The anti-corrosion passivation solution of the present application introduces rare earth modified heteropoly acid, and the corrosion resistance of the hot-dip galvanized sheet after treatment is significantly improved, which can extend the service life of the hot-dip galvanized sheet;

[0022] (3) The anti-corrosion passivation liquid of the present application uses a compound of rare earth modified heteropoly acid, phosphate, nitrate and nano-silicon dioxide, which can significantly improve the corrosion resistance of the anti-corrosion passivation liquid and obtain better stability. DETAILED DESCRIPTION

[0023] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0024] The terms "including" and "having" and any variations thereof in the specification and claims of the present application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.

[0025] The present application provides a chromium-free hot-dip galvanizing anticorrosion passivation liquid, which is made of rare earth modified heteropoly acid, water-based resin, phosphate, nitrate, nano silicon dioxide and polar solvent.

[0026] The anti-corrosion passivation liquid of the present application can form a dense protective film on the surface of the galvanized layer while containing no chromium element, thereby reducing the impact of chromium emissions on the environment and human health, being more environmentally friendly and more in line with current environmental protection requirements.

[0027] The anti-corrosion passivation liquid of the present application introduces rare earth modified heteropoly acid, and the corrosion resistance of the hot-dip galvanized sheet treated therewith is significantly improved, and the service life of the hot-dip galvanized sheet can be extended.

[0028] The anti-corrosion passivation liquid of the present application is compounded with rare earth modified heteropoly acid, phosphate, nitrate and nano-silicon dioxide, which can significantly improve the corrosion resistance of the anti-corrosion passivation liquid and obtain better stability.

[0029] The preparation method of rare earth modified heteropoly acid material is prior art and can also be obtained by purchase. This application provides a method of rare earth modified heteropoly acid for reference.

[0030] Preparation of rare earth modified heteropoly acid: a metal precursor, an alcohol solution and a strong acid are mixed in a certain proportion, and then a rare earth element compound, a heteropoly acid and a surfactant are added to obtain a mixture, the mixture is subjected to ultrasonic dispersion treatment for a period of time, and then allowed to stand to form a gel, and the gel is dried and ground to obtain a rare earth modified heteropoly acid.

[0031] Specifically, the metal precursor can be tetraethyl orthosilicate, the alcohol solution can be ethanol or propanol, the strong acid can be nitric acid, sulfuric acid or hydrochloric acid, and the rare earth element compound such as La(NO 3 ) 3 or Ce(NO 3 ) 4 The heteropoly acid may be tungstophosphoric acid, molybdophosphoric acid or tungstosilico heteropoly acid.

[0032] The synthesis method of rare earth modified heteropoly acid is a relatively mature existing technology. Rare earth elements are introduced into the molecular structure of heteropoly acid. Rare earth elements form new coordination bonds with heteroatoms (such as phosphorus) in heteropoly acid to form a heteropoly acid structure with a specific geometric shape. Stable MO bonds are formed between rare earth elements and oxygen atoms in heteropoly acid. This bonding can serve as an acidic active center to improve the stability and repeated practicality of the catalyst.

[0033] The introduction of rare earth elements can change the electronic structure of heteropolyacids, enhance their acidity and redox properties. The introduction of rare earth elements will form novel structures and compositions, which will give the compounds unique properties, increase the specific surface area, pore size and thermal stability of heteropolyacids, and produce unexpected effects in more fields.

[0034] Finally, the rare earth modified heteropoly acid has better dispersion, uniform particle size, and larger particle size, which is conducive to its active effect.

[0035] The chromium-free hot-dip galvanizing anticorrosion passivation liquid of the present application is made of 5% to 20% rare earth modified heteropoly acid, 12% to 25% water-based resin, 3% to 10% phosphate, 5% to 15% nitrate, 0.1% to 0.5% nano silicon dioxide, and the remainder polar solvent, calculated by mass fraction.

[0036] The content of rare earth modified heteropoly acid has a great influence on the corrosion resistance of the anti-corrosion passivation liquid. Through continuous experiments, it is found that when the addition amount of rare earth modified heteropoly acid is controlled within the range of 5% to 20% by mass fraction, a stable anti-corrosion passivation liquid can be formed and good corrosion resistance can be obtained.

[0037] In some preferred embodiments, the chromium-free hot-dip galvanizing anti-corrosion passivation liquid of the present application is made of 5% rare earth modified heteropoly acid, 12% water-based resin, 10% phosphate, 15% nitrate, 0.1% nano-silicon dioxide, and the remainder polar solvent, by mass fraction.

[0038] Waterborne resins are a class of polymer materials that use water as a solvent or dispersant. These materials are generally more environmentally friendly than traditional solvent-based resins, reduce volatile organic compounds, and can be dispersed or dissolved in water, but after drying they usually become insoluble in water to form a strong film layer.

[0039] In some embodiments, the water-based resin may be a water-based acrylic resin, a water-based polyurethane resin, a water-based epoxy resin, a water-based alkyd resin, a water-based polyester resin, a water-based phenolic resin, a water-based amino resin, or the like.

[0040] Water-based resin can react on the surface of the galvanized layer to form a dense protective film, which enhances the corrosion resistance of the galvanized layer. The water-based resin conversion film is a porous structure with good adsorption properties, which can significantly improve the adhesion and corrosion resistance of the coating to the base metal. The metal surface treated with water-based resin is smoother and more uniform, with better appearance quality, which can improve the aesthetics and market competitiveness of the product. Water-based resin does not contain harmful chemicals, so it is more environmentally friendly and reduces the impact on the environment and human health.

[0041] In some embodiments, the phosphate is such as sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, ammonium phosphate, ammonium dihydrogen phosphate, sodium hexametaphosphate, and the like.

[0042] Phosphates can react with zinc to form zinc phosphates, which can form a protective film on the surface of the galvanized layer and enhance the corrosion resistance of the galvanized layer. Phosphate treatment can improve the adhesion between the galvanized layer and the subsequent coating, which is crucial to improving the durability and protective properties of the coating. Finally, the surface hardness of the galvanized sheet treated with phosphate is improved, which can better resist friction and wear and help extend the service life of the metal.

[0043] In some embodiments, the nitrate is sodium nitrate, potassium nitrate, ammonium nitrate, calcium nitrate, magnesium nitrate, barium nitrate, and the like.

[0044] Nitrates can act as oxidants under acidic conditions, helping to form an oxide film on the surface of the galvanized layer, improving the corrosion resistance of the galvanized layer, and can promote the formation of a passivation film and enhance the adhesion and stability of the film.

[0045] Nano-silicon dioxide forms a colloidal solution after being added to the anti-corrosion passivation liquid. After being applied to the galvanized sheet and dried, the passivation liquid solidifies to form a gel, which has a strong adhesion to the galvanized sheet. The gel formed by nano-silicon dioxide also has a certain isolation effect, preventing external moisture and gas from penetrating into the surface of the galvanized layer, and has a certain auxiliary anti-corrosion effect.

[0046] Nano-silicon dioxide exists in the gel as polar particles, so in addition to adsorbing other components in the passivation layer on the surface of the galvanized sheet, it can also act as a medium, tightly combining with the outer coating of the passivation layer to improve the coating performance. After adding nano-silicon dioxide, the effect of silica gel makes the passivation film on the surface of the passivated product more uniform, and even if the adsorption of fingerprints is large, it is not easy to be noticed by people, thereby improving the product's anti-fingerprint performance.

[0047] In some embodiments, the polar solvent is water, methanol, ethanol, acetone, acetonitrile, acetic acid, tetrafluoroethane, ethyl acetate, dimethyl sulfoxide, ethylene glycol, glycerol, formic acid, pyridine, ammonia, and the like.

[0048] The present application also provides a method for preparing a chromium-free hot-dip galvanizing anti-corrosion passivation liquid: a certain amount of phosphate and nitrate are dispersed in a polar solvent, rare earth modified heteropoly acid is added and evenly dispersed to obtain a first solution; nano silicon dioxide is dispersed in an aqueous resin to form a second solution; the first solution is added dropwise to the second solution under continuous stirring, continuous stirring is performed to mix the two solutions evenly, and the mixture is allowed to stand for more than 24 hours for use.

[0049] The preparation method of the chromium-free hot-dip galvanizing anti-corrosion passivation liquid of the present application is simple, easy to operate, suitable for process-based large-scale production, does not contain harmful substances, has little harm to human health and the environment, and is highly economical.

[0050] Example 1

[0051] A corrosion-resistant passivation liquid with a rare earth modified heteropoly acid content of 5% is prepared. The raw materials of the corrosion-resistant passivation liquid are composed by mass fraction: 5% rare earth modified heteropoly acid, 12% water-based acrylic resin, 10% sodium phosphate, 15% sodium nitrate and 0.1% nano-silicon dioxide, and the balance is water. The preparation steps are as follows:

[0052] A certain amount of sodium phosphate and sodium nitrate are dissolved in water, and rare earth modified heteropoly acid is added to obtain a first solution after dissolution; water-based acrylic resin is added to nano-silicon dioxide while stirring, and stirring is continued for 20 minutes to obtain a second solution. While stirring, the first solution is gradually added dropwise to the second solution, and stirring and mixing are continued for 4 hours, and the solution is allowed to stand for more than 24 hours for use.

[0053] Example 2

[0054] A corrosion-resistant passivation liquid having a rare earth modified heteropoly acid content of 10% was prepared, wherein the raw materials of the corrosion-resistant passivation liquid were composed by mass fraction: 10% rare earth modified heteropoly acid, 12% water-based acrylic resin, 10% sodium phosphate, 15% sodium nitrate and 0.1% nano-silicon dioxide, and the balance was water. The remaining preparation steps were consistent with the preparation steps of Example 1.

[0055] Example 3

[0056] A corrosion-resistant passivation liquid having a rare earth modified heteropoly acid content of 15% was prepared, wherein the raw materials of the corrosion-resistant passivation liquid were composed by mass fraction: 15% rare earth modified heteropoly acid, 12% water-based acrylic resin, 10% sodium phosphate, 15% sodium nitrate and 0.1% nano-silicon dioxide, and the balance was water. The remaining preparation steps were consistent with the preparation steps of Example 1.

[0057] Example 4

[0058] A corrosion-resistant passivation liquid having a rare earth modified heteropoly acid content of 20% was prepared, wherein the raw materials of the corrosion-resistant passivation liquid were composed by mass fraction: 20% rare earth modified heteropoly acid, 25% water-based acrylic resin, 3% sodium phosphate, 5% sodium nitrate and 0.5% nano-silicon dioxide, and the balance was water. The remaining preparation steps were consistent with the preparation steps of Example 1.

[0059] Comparative Example 1

[0060] The difference between Comparative Example 1 and Example 1 is that no rare earth modified heteropoly acid is added to the prepared passivation solution, and the remaining preparation steps are consistent with the preparation steps of Example 1.

[0061] Comparative Example 2

[0062] The difference between Comparative Example 2 and Example 1 is that the rare earth modified heteropoly acid in the prepared passivation solution is replaced by heteropoly acid of the same mass, and the remaining preparation steps are consistent with the preparation steps of Example 1.

[0063] Comparative Example 3

[0064] The difference between Comparative Example 2 and Example 1 is that the rare earth modified heteropoly acid in the prepared passivation solution is replaced by a mixture of heteropoly acid and rare earth compound of the same mass, and the remaining preparation steps are consistent with the preparation steps of Example 1.

[0065] Comparative Example 4

[0066] The difference between Comparative Example 4 and Example 1 is that no phosphate is added to the prepared passivation solution, and the remaining preparation steps are consistent with the preparation steps of Example 1.

[0067] Comparative Example 5

[0068] The difference between Comparative Example 5 and Example 1 is that no nitrate is added to the prepared passivation solution, and the remaining preparation steps are consistent with the preparation steps of Example 1.

[0069] Comparative Example 6

[0070] The difference between Comparative Example 6 and Example 1 is that no nano-silicon dioxide is added to the prepared passivation solution, and the remaining preparation steps are consistent with the preparation steps of Example 1.

[0071] Performance Testing

[0072] 1. Pretreatment of hot-dip galvanized sheet: Before passivation, the hot-dip galvanized sheet needs to be degreased. Prepare a degreasing solution with a mass fraction of 20%, heat it to 80°C for use, wash off the grease on the surface of the hot-dip galvanized steel sheet with a rag, then rinse it with plenty of water (water film is evenly distributed on the surface), and finally rinse it three times with distilled water, place it in an oven at 100°C for 2 minutes to dry, take it out and cool it for use.

[0073] 2. Preparation of passivation film: set the oven temperature to 150°C and keep it warm for standby use; wash the hot-dip galvanized steel sheet, then place the hot-dip galvanized steel sheet on a flat suction plate, use a straw to absorb a certain amount of the anti-corrosion passivating agent prepared in Examples 1 to 4 and Comparative Examples 1 to 6 and evenly coat it on the surface of the hot-dip galvanized steel sheet; put the hot-dip galvanized steel sheet coated with the anti-corrosion passivating agent into an oven and dry it for a certain period of time, and take it out after passivation film formation.

[0074] 3. Sample preparation: Cut each hot-dip galvanized steel plate after passivation into test pieces of the same specifications with a shearing machine, and cut each hot-dip galvanized steel plate treated with an anti-corrosion passivation liquid into 8 test samples. Melt paraffin and rosin in a resistance furnace at a mass ratio of 1:1, and seal the sides and backs of the hot-dip galvanized plates of each test sample with the melted paraffin and rosin.

[0075] 4. Salt spray test: Salt spray test is an environmental test that uses artificial simulated salt spray environment conditions created by salt spray test equipment to examine the corrosion resistance of products or metal materials. There are two main categories: the first category is natural environment exposure test, and the other category is artificial accelerated simulated salt spray environment test. Salt spray test has been widely used to determine the uniformity and porosity of the thickness of various protective coatings (platings), and is one of the effective methods for screening coatings (platings). The concentration of chloride ions in the salt spray in the salt spray test chamber is much higher than that in the marine climate air, and the oxygen concentration in the salt spray is close to saturation. Therefore, the material corrodes faster in the salt spray, and the corrosion resistance of the material can be tested in a shorter time, shortening the test time.

[0076] GB / T10125-1997 specifies in detail the operation methods of neutral salt spray test (NSS), acetic acid salt spray test (AASS) and copper accelerated acetic acid salt spray test (CASS). Corrosion resistance is tested according to the methods and conditions specified in GB / T10125-1997, and then the corrosion results are evaluated according to the provisions of GB12335-90 (expressed as the percentage of the corrosion area after 120h and 216h to the total area). The smaller the corrosion area, the better the effect of the anti-corrosion passivation solution.

[0077] 5. Paint film adhesion test: The paint film adhesion of the passivation film is an important indicator for evaluating the performance of the passivation film in the later stage, and needs to be tested and evaluated. It is evaluated according to the national standard "GB / T9286-1998 Cross-cut Test for Paint and Varnish Film". The grade is evaluated according to the proportion of the coating film shedding area, compared with the standard, and the test results are analyzed. The film adhesion grade is shown in Table 1.

[0078] Table 1 Evaluation of film adhesion level Phenomenon grade The film layer is not damaged or peeled off 5 The film layer is slightly damaged and not falling off 4 The film layer is slightly damaged and slightly peeled off 3 The film layer is obviously damaged and slightly peeled off 2 The film layer is obviously damaged or peeled off 1

[0079] 6. Heat resistance test: According to the change of the sample at 300℃ for 20 minutes, if the change of the color difference between the front and back is less than 4, and the film does not have bubbles, fall off, or powdering, it is grade A. If the change of the color difference between the front and back is greater than 4 and less than 8, and the film does not have bubbles, fall off, or powdering, it is grade B. If the change of the color difference between the front and back is greater than 8, and the film does not have bubbles, fall off, or powdering, it is grade C. If the film has bubbles, fall off, or powdering, it is grade D. At present, the heat resistance of galvanized coatings is generally required to be grade B or C.

[0080] 7. Water resistance test: Deionized water at 100℃ is dripped onto the sample for testing. If there is no water mark on the sample, it is Class A; if there is slight water mark, it is Class B. If there is obvious water mark, it is Class C. At present, the water resistance of hot-dip galvanized coating is generally required to be Class B.

[0081] The results of the salt spray test, paint film adhesion test, heat resistance test and water resistance test of each embodiment and each comparative example are recorded in the following Table 2.

[0082] Table 2 Performance test results of each embodiment and each comparative example

[0083] From the analysis of the performance test results of each embodiment and each comparative example, it can be seen that the chromium-free hot-dip galvanizing anti-corrosion passivation liquid of the present application can effectively resist corrosion, and can obtain good heat resistance and water resistance, and has good paint film adhesion.

[0084] Analysis of the performance test results of Examples 1 to 4 shows that different contents of rare earth modified heteropoly acid have different performance effects. In the anti-corrosion passivation solution, as the content of rare earth modified heteropoly acid increases, the adhesion effect of the paint film decreases, and the heat resistance and water resistance also decrease. Therefore, an addition amount of 5% of rare earth modified heteropoly acid is more appropriate.

[0085] By analyzing the performance test results of Example 1 and Comparative Examples 1 to 3, it is found that rare earth elements are introduced into the structure of heteropoly acids to form new coordination bonds, giving the compounds unique properties. When added to the anti-corrosion passivation liquid, the corrosion resistance effect is better than that of the heteropoly acids added alone, or the mixture of heteropoly acids and rare earth compounds.

[0086] By analyzing Example 1 and Comparative Examples 4 to 6, the anti-corrosion passivation liquid of the present application, which is compounded with rare earth modified heteropoly acid, phosphate, nitrate and nano-silicon dioxide, has the best corrosion resistance and can obtain the best adhesion, heat resistance and water resistance.

[0087] The chromium-free hot-dip galvanizing anti-corrosion passivation liquid of the present application can form a stable passivation film on the hot-dip galvanizing surface, avoiding the occurrence of flower blooming, white powder falling, etc. The formula components that do not contain harmful chromium elements are used, making the production process and products more environmentally friendly and safe. The production process is simple and easy to understand, and has certain economic adaptability.

[0088] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments. The above embodiments and the description only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application. These changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.

Claims

1. A chromium-free hot-dip galvanizing anticorrosion passivation solution, characterized in that: It is made of rare earth modified heteropoly acid, water-based resin, phosphate, nitrate, nano-silica and polar solvent.

2. The chromium-free hot-dip galvanizing anticorrosion passivation solution according to claim 1, characterized in that: The added amount of the rare earth modified heteropoly acid is 5% to 20% of the total mass of the anti-corrosion passivation liquid.

3. The chromium-free hot-dip galvanizing anticorrosion passivation solution according to claim 2, characterized in that: Calculated by mass fraction, it is made of 5% to 20% rare earth modified heteropoly acid, 12% to 25% water-based resin, 3% to 10% phosphate, 5% to 15% nitrate, 0.1% to 0.5% nano silicon dioxide, and the balance polar solvent.

4. The chromium-free hot-dip galvanizing anticorrosion passivation solution according to claim 3, characterized in that: Calculated by mass fraction, it is made of 5% rare earth modified heteropoly acid, 12% water-based resin, 10% phosphate, 15% nitrate, 0.1% nano silicon dioxide, and the balance polar solvent.

5. The chromium-free hot-dip galvanizing anticorrosion passivation solution according to claim 2, characterized in that: The rare earth modified heteropoly acid is prepared from a metal precursor, a rare earth element compound, a heteropoly acid and other additives by a sol-gel method.

6. The chromium-free hot-dip galvanizing anticorrosion passivation solution according to claim 5, characterized in that: The preparation method of the rare earth modified heteropoly acid is as follows: the metal precursor, alcohol solution and strong acid are mixed in a certain proportion, and then the rare earth element compound, the heteropoly acid and surfactant are added to obtain a mixture, the mixture is subjected to ultrasonic dispersion treatment for a period of time, and allowed to stand to form a gel, and the dried gel is ground to obtain the rare earth modified heteropoly acid.

7. The chromium-free hot-dip galvanizing anticorrosion passivation solution according to claim 6, characterized in that: The rare earth element compound is La(NO3)3 or Ce(NO3)4, and the heteropoly acid is any one of phosphotungstic heteropoly acid, phosphomolybdic heteropoly acid and silicotungstic heteropoly acid.

8. The chromium-free hot-dip galvanizing anticorrosion passivation solution according to claim 1, characterized in that: The water-based resin is any one or more combinations of water-based acrylic resin, water-based polyurethane resin, water-based epoxy resin, water-based alkyd resin, water-based polyester resin, water-based phenolic resin, and water-based amino resin; the phosphate is any one or more combinations of sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and sodium hexametaphosphate; the nitrate is any one or more combinations of sodium nitrate, potassium nitrate, ammonium nitrate, calcium nitrate, magnesium nitrate, and barium nitrate.

9. A method for preparing a chromium-free hot-dip galvanizing anticorrosion passivation solution, characterized in that: The phosphate and nitrate are dispersed in a polar solvent, and rare earth modified heteropoly acid is added and evenly dispersed to obtain a first solution; nano silicon dioxide is dispersed in an aqueous resin to form a second solution; the first solution is added dropwise to the second solution under continuous stirring, and the mixture is continuously stirred to be evenly mixed, and the mixture is allowed to stand for a period of time for use.

10. The method for preparing the chromium-free hot-dip galvanizing anticorrosion passivation solution according to claim 9, characterized in that: Let stand for more than 24 hours.